Rediscovery of Lophiodes triradiatus (Lloyd, 1909), a senior synonym of L. infrabrunneus Smith and Radcliffe (Lophiiformes: Lophiidae) - Ho, Hsuan-Ching; Bineesh, K. K.; Akhilesh, K. V. (Zootaxa, 2014)
Examination of the holotype and three recently collected additional specimens from the Indian Ocean has revealed that Lophius triradiatus Lloyd, 1909 (now under Lophiodes)  is a valid species and a senior synonym of Lophiodes infrabrunneus Smith & Radcliffe, 1912 and Lophiodes abdituspinus Ni, Wu & Li, 1990. A detailed description of the additional specimens is provided.